An AI-Based Mobile Application for Personalized Learning in Secondary Education - Ellysha Dwiyanthi Kusuma; Lianny Wydiastuty Kusuma; Hartana Wijaya; Arya Bodhi Yuardi; Michael Sidharta Dharma (Department of Informatics Engineering, 2026)
The development of Artificial Intelligence (AI) provides opportunities to support personalized learning, particularly at the secondary school level, where students have diverse learning needs. This study aims to develop an AI-assisted mobile application prototype to support personalized learning and assist teachers in monitoring student progress. The research adopts a Research and Development (RD) approach, which includes stages of user needs analysis, system design, prototype development, and user evaluation. The application was developed in two versions: a student application and a teacher application, both implemented on Android devices. The student application provides features such as a learning dashboard, adaptive quizzes, learning analytics, feedback, and rule-based learning recommendations derived from student performance, while the teacher application offers class monitoring, grade input, and learning material upload functionalities. The evaluation involved 43 students and 3 teachers using usability questionnaires. Results indicate that more than 85% of students found the application easy to use and beneficial in supporting their learning, while teachers reported that the system supports monitoring and instructional activities. These findings suggest that the proposed application is feasible and well-accepted as a personalized learning support tool. However, further studies are required to evaluate its impact on learning outcomes using more rigorous experimental methods.